AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT BIJI TERATAI (Nymphaea pubescens Willd) AKIBAT PEMANASAN - Yuspihana Fitrial (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
The purposes of this study were to evaluate the in uence of heating temperature, 100 ˚C and 121 ˚C (the autoclave temperature) on antibacterial activity and stability of water lily seed ethyl acetate extract. Research was initiated with water lily seed extract using multistage maceration extraction method based on solvent polarity level. Extraction stages beginning with a solvent hexane (non polar), then with ethyl acetate (semi-polar) so that theobtained ethyl acetate extract. In ethyl acetate extracts were subjected to heating at 100 ˚C and 121 ˚C. Each extract that has been treated, tested for antibacterial activity with tested bacteria E. coli and S. Typhimurium by using agar well diffusion method. Observations on the stability of fractions contained in the ethyl acetate extract from the treatment given, performed by using TLC (Thin Layer Chromatographi) with a mobile phase of hexane and ethyl acetate (7:3). The activities of each fraction were tested quantitatively by agar well diffusion method. Based on the results of these studies showed that heating affect the antibacterial activity of ethyl acetate extracts. The higher the temperature, decreased antibacterial activity, however at a temperature of 121 ˚ C, ethyl acetate extracts still have antibacterial activity. The process of heating effect on the stability of the ethyl acetate extract fractions. The fractions that too act as an antibacterial were 5 and 6 that relatively more polar than the fraction of 7,8,9,10 and 11. The both fractions was not stable against heating temperature of 100 ˚C and 121 ˚C.Key words: antibacterial, ethyl acetate extract, fraction, temperature